2010
DOI: 10.1111/j.1600-051x.2010.01619.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on chronic periodontitis: a randomized pilot study

Abstract: The results suggest that ATV might have beneficial effects on bone alveolar loss and tooth mobility in subjects with periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
92
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 47 publications
4
92
0
3
Order By: Relevance
“…26 ATV and SMVhave been found to have osteoblastic actions in animal and human studies. 13-16 ,Fajardo et al 27 in a study found that ATV administration improved periodontal parameters, including PD, CAL and mobility over a 3-month period. Morris et al 28 showed effective IBD fill and a greater decrease in PD and RAL gain compared to the control group when injectable SMV was used in three-walled periodontal IBDs, class II furcations defects and edentulous alveolar ridges in beagle dogs.…”
Section: Discussionmentioning
confidence: 99%
“…26 ATV and SMVhave been found to have osteoblastic actions in animal and human studies. 13-16 ,Fajardo et al 27 in a study found that ATV administration improved periodontal parameters, including PD, CAL and mobility over a 3-month period. Morris et al 28 showed effective IBD fill and a greater decrease in PD and RAL gain compared to the control group when injectable SMV was used in three-walled periodontal IBDs, class II furcations defects and edentulous alveolar ridges in beagle dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Statins could attenuate the inflammation-related systemic effects. Controlled clinical trials using systemically or locally administered statins have shown significant improvements of periodontal sequelae [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported a correlation between statin use and improvement of clinical signs of periodontal disease including bone defect, tooth movement, and tooth loss 15–17 . This prompted a hypothesis that statins might directly affect osteoclasts that are responsible for periodontal bone loss.…”
mentioning
confidence: 99%